The values of (x, y) are (-5, 1), if the equations
and
are solved by elimination method.
Step-by-step explanation:
The given is,
................................(1)
.....................................(2)
Step:1
Equation (2) is multiplied by -1 ( Eqn (2) × -1 )
..................................(3)
Step:2
Substrate the equation (1) and equation (3),
![x-5y=-10](https://tex.z-dn.net/?f=x-5y%3D-10)
![x-y=-6](https://tex.z-dn.net/?f=x-y%3D-6)
( - )
After the Subtraction equation becomes,
![(x-x)+(-5y+y)=(-10+6)](https://tex.z-dn.net/?f=%28x-x%29%2B%28-5y%2By%29%3D%28-10%2B6%29)
![(0)+(-4y)=(-4)](https://tex.z-dn.net/?f=%280%29%2B%28-4y%29%3D%28-4%29)
![-4y=-4](https://tex.z-dn.net/?f=-4y%3D-4)
![y=1](https://tex.z-dn.net/?f=y%3D1)
Step:3
By using y value find value of x,
![x-5y=-10](https://tex.z-dn.net/?f=x-5y%3D-10)
![x-(5)(1)=-10](https://tex.z-dn.net/?f=x-%285%29%281%29%3D-10)
![x=-10+5](https://tex.z-dn.net/?f=x%3D-10%2B5)
![x=-5](https://tex.z-dn.net/?f=x%3D-5)
Step:4
Check for solution,
![-x+y=6](https://tex.z-dn.net/?f=-x%2By%3D6)
![-(-5)+1=6](https://tex.z-dn.net/?f=-%28-5%29%2B1%3D6)
![6=6](https://tex.z-dn.net/?f=6%3D6)
Both sides are equal so answer is corrected
Result:
The values of (x, y) are (-5, 1), if the equations
and
are solved by elimination method.